Energy-Efficient Approach Based on 3G Background Traffic Shaping - Jianwu Zhang; Jie Yuan (Dianxin kexue)
With the development of mobile applications, the massive background data transfers may seriously burden the user equipment and reduce the lifetime of battery. In order to reduce the energy consumption of this background traffic, a new energy-efficient approach based on traffic shaping, that uses some static network parameters such as inactivity timer, buffer threshold, was proposed. The simulation results show that the approach can save 32％to 63％Cof the total energy consumption.